PENGEMBANGAN COMPACT DISC INTERAKTIF DENGAN SOFTWARE AUTOPLAY MEDIA STUDIO 8 PADA MATERI OPERASI HITUNG BENTUK ALJABAR DI MTSN PADANG LUAR - Idris, Idris (Jurnal Pembelajaran MIPA, 2014)
This reseach aims to construct an interactive CD as media instructional for mathematics at the algebra arithmetic operations are valid and practical. This development research uses 4-D model, the definition, design, development and disseminate. This research is only done through the development stage. In the definition phase is done analyzing the syllabus and students. Furthermore, the design of a prototype interactive CD as well as a research instrument validation sheet and questionnaire. At this stage of development, interactive CD tested for validity by experts, and performed limited testing to see the practicality. This research has produced an interactive CD media with valid category based on the results of the validity test is 81.16% and get a positive response from students as test subjects practicalities is 86.21%, so practically categorized interactive CD media.Keywords: Interactive CDs, Autoplay media studio 8, Operating arithmetic algebraic